Immune evasion by TGFβ-induced miR-183 repression of MICA/B expression in human lung tumor cells. (3rd April 2019) - Trinh, Thu Le; Kandell, Wendy M.; Donatelli, Sarah S.; Tu, Nhan; Tejera, Melba M.; Gilvary, Danielle L.; Eksioglu, Erika A.; Burnette, Alexis; Adams, William A.; Liu, Jinhong; Teer, Jamie K.; Djeu, Julie Y.; et al.
ABSTRACT: Immune escape is a hallmark of cancer. In human lung cancer, we have identified a unique microRNA (miR)-based pathway employed by tumor cells to repress detection by immune cells via the NKG2D-MICA/B receptor-ligand system. MICA/B is readily induced by cell transformation and serves as a danger signal and ligand to alert NK and activated CD8 + T cells. However, immunohistochemical analysis indicated that human lung adenocarcinoma and squamous cell carcinoma specimens express little MICA/B while high levels of miR-183 were detected in both tumor types in a TCGA database. Human lung tumor cell lines confirmed the reverse relationship in expression of MICA/B and miR-183. Importantly, a miR-183 binding site was identified on the 3ʹuntranslated region (UTR) of both MICA and MICB, suggesting its role in MICA/B regulation. Luciferase reporter constructs bearing the 3ʹUTR of MICA or MICB in 293 cells supported the function of miR-183 in repressing MICA/B expression. Additionally, anti-sense miR-183 transfection into H1355 or H1299 tumor cells caused the upregulation of MICA/B. Abundant miR-183 expression in tumor cells was traced to transforming growth factor-beta (TGFβ), as evidenced by antisense TGFβ transfection into H1355 or H1299 tumor cells which subsequently lost miR-183 expression accompanied by MICA/B upregulation. Most significantly, anti-sense miR-183 transfected tumor cells became more sensitive to lysis by activated CD8 + T cells that express high levels of NKG2D. Thus, high miR-183 triggered by TGFβ expressed in lung tumor cells can target MICA/B expression to circumvent detection by NKG2D on immune cells.